The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.pharmthera.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte integrins: Role in leukocyte recruitment and as therapeutic targets in inflammatory disease

Abstract: Infection or sterile inflammation triggers site-specific attraction of leukocytes. Leukocyte recruitment is a process comprising several steps orchestrated by adhesion molecules, chemokines, cytokines and endogenous regulatory molecules. Distinct adhesive interactions between endothelial cells and leukocytes and signalling mechanisms contribute to the temporal and spatial fine-tuning of the leukocyte adhesion cascade. Central players in the leukocyte adhesion cascade include the leukocyte adhesion receptors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
226
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(231 citation statements)
references
References 266 publications
(329 reference statements)
2
226
0
3
Order By: Relevance
“…21 We have previously shown that monocyte traffic to the DRG is associated with severe DRG pathology, as well as a loss of intraepidermal nerve fiber density. 2 Herein, we used natalizumab to determine the effect of blocking leukocyte traffic on DRG pathology.…”
Section: Discussionmentioning
confidence: 95%
“…21 We have previously shown that monocyte traffic to the DRG is associated with severe DRG pathology, as well as a loss of intraepidermal nerve fiber density. 2 Herein, we used natalizumab to determine the effect of blocking leukocyte traffic on DRG pathology.…”
Section: Discussionmentioning
confidence: 95%
“…Due to their critical role in leukocyte recruitment, leukocyte integrins have emerged as potential therapeutic targets in several inflammatory diseases, and some antileukocyte integrin therapeutics have reached the clinic. 118,119 Similarly, the essential role of aIIbb3 in platelet aggregation and thrombus formation has led to aIIbb3 antagonists used to treat cardiovascular diseases. 7,119 That said, mechanism-based toxicities, ascribable to the effects of complete blockade of integrins, have limited the utility of such therapies.…”
Section: Translational Implicationsmentioning
confidence: 99%
“…114,115 Additional work is required to determine whether inhibiting RIAM can ameliorate diseases that depend on leukocyte integrin functions, eg, psoriasis and inflammatory bowel disease. 118,119 Because RIAM-deficient mice are viable, fertile, and healthy, [113][114][115] amelioration of disease models would portend a potential therapeutic benefit in blocking RIAM or the signaling events that enable its functions. Reverse genetic experiments (mutating a gene and analyzing resulting phenotype) in mice revealed that RIAM is dispensable for platelet function and associated with mild neutrophil and lymphocyte function defects.…”
Section: Translational Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a leukocyte adhesion receptor of the β2-integrin family, which consists of major players in the leukocyte adhesion cascade (Mitroulis et al 2015). Although normally expressed only in neutrophils and monocytes, Mac-1 has been found to play an important role in MP-driven metastasis of murine hepatocarcinoma cells (Ma et al 2013).…”
Section: Mac-1 Integrinsmentioning
confidence: 99%